A study of the excited electronic states of normal and fully deuterated furan by photoabsorption spectroscopy and high-level ab initio calculations - Holland, David M.P.; Gromov, Evgeniy; Wormit, Michael; Dreuw, Andreas (Journal of molecular spectroscopy, 2015)
The photoabsorption spectra of C4H4O and C4D4O have been measured between ∼5.5 and 17.7eV using a synchrotron radiation-based Fourier transform spectrometer. In addition to several broad bands due to transitions into valence states, the spectra exhibit numerous sharp bands associated with Rydberg states belonging to series converging onto the X̃2A2 or the Ã2B1 state limits. Vertical excitation energies and oscillator strengths have been computed using the second- and third-order algebraic-diagrammic construction polarisation propagator methods (ADC(2) and ADC(3)), and the equation-of-motion coupled-cluster method at the level of singles and doubles model (EOM-CCSD). Adiabatic excitation energies have been estimated using previously computed corrections.
Gesehen am 12.12.2017